Serviços telemáticos em uma rede de transporte público baseados em veículos conectados e dados abertos - Diniz Junior, Paulo Carvalho (2017)
Smart city is a very trendy concept today. It defines a type of urban development capable of reducing environmental impacts, enhancing current models of access to natural resources, better transportation systems, waste management, residential climatization and, above all, energy management (production and distribution). The huge data volume produced by smart cities offers a great opportunity to analyze, understand and improve the way cities work and grow. This explosion in the amount of digital information has elevated the importance of learning from data to a higher level. This document aims at describing a methodology for acquiring and exploring data from one of the most important pillars of smart cities: the public transportation system. How to acquire, store and use such data in order to provide to all stakeholders telematics services with high added value is the problem that is sought to solve in this work. Five telematics services proof of concept are proposed: assessment of current network coverage followed by the proposal of some new bus lines; indirect evaluation of buses’ passengers occupation during the day; geofence with geographical boundaries according to itineraries; speed alert and maintenance reminder services. The results are very coherent and promising, opening up a wide range of possible future work to be explored.